1.5(2g-3)=-4(g+1)

Simple and best practice solution for 1.5(2g-3)=-4(g+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.5(2g-3)=-4(g+1) equation:



1.5(2g-3)=-4(g+1)
We move all terms to the left:
1.5(2g-3)-(-4(g+1))=0
We multiply parentheses
3g-(-4(g+1))-4.5=0
We calculate terms in parentheses: -(-4(g+1)), so:
-4(g+1)
We multiply parentheses
-4g-4
Back to the equation:
-(-4g-4)
We get rid of parentheses
3g+4g+4-4.5=0
We add all the numbers together, and all the variables
7g-0.5=0
We move all terms containing g to the left, all other terms to the right
7g=0.5
g=0.5/7
g=0.5/7

See similar equations:

| -1/5t+-2=4 | | x+6/2=5/7 | | 30x+30(x+5)=3450 | | 7+4=21-n | | P=BxR;=$302,000,R=0.05 | | -c/4-7=14 | | F(x)=5x1/3.5 | | M+5m=-18 | | 0.2(6-3k)=0.4(5k-10) | | 7(5v-8)=-26-9v | | 7÷4=n-21 | | 80+25+x=180 | | 3/7x+1/3=x | | 21+2y-8=10y-11-4y | | 21,494=35,000•b | | (2x-2)+90+(x+5)=180 | | 18.5x=(121/x)+7.5 | | w· 2/3= 1/4 | | 16=x^2-3x | | 2x+×=9+9 | | 11-3x=40 | | -5/2(8y-2=5)10-y | | .5=31;q=13 | | 10.5=2x+x | | (x/2)+1=6 | | x+x-7=24 | | x2+8x+15=320 | | 87=y+12 | | 6v-6v=-6+2v | | 2(3h-2)=3(2h+8) | | 4(x+5)=4x=5 | | 160+80+x=90 |

Equations solver categories